PERANCANGAN SISTEM PEMANAS AIR MENGGUNAKAN SISTEM KENDALI PID - Parmadi Putra, I.W.; Arta Wijaya, I. W.; Budiastra, I.N. (Jurnal SPEKTRUM, 2020)
As the technology advances in control system grow rapidly, especially those involved with water temperature, there is an increased demand for a control system that is able to provide precisely stable temperature value. The commonly used systems nowadays are still using the ON/OFF control system for it is relatively affordable and simple, but unfortunately numerous errors are still found and it is not yet able to provide precise data. Therefore, a PID control system was developed to address this issue. In this study, Arduino UNO temperature control was used as data acquisition system, and LM35 temperature sensor was used to detect the temperature recognized by signal conditioning. From the signal conditioning, the driver will then control the heater in order to obtain a precise temperature. This PID system utilized a water-resistant temperature sensor. In this study, the heater was treated by means of controlling the PID temperature which ranged from 69oC to 70.5oC. Another test was done by comparing the temperature value detected by the device’s temperature sensor with an external digital thermometer which was placed in the same container. The temperature value detected by the device’s temperature sensor had a difference of ± 1,300C compared to the digital thermometer.